The effectiveness and application of Urtica dioica (stinging nettle) for musculoskeletal disorders: a systematic review and meta-analysis - Ahmad Zawawi, Sahira Syamimi; Zamli, Zaitunnatakhin; Saad, Nurulwahida (IIUM Press, International Islamic University Malaysia, 2023)
Musculoskeletal disorders (MSDs) are injuries of muscles, bones, tendons, joints, and ligaments commonly treated with medications like non-steroidal anti-inflammatory drugs and analgesic. However, undesired adverse effects with prolonged use have been reported. Urtica dioica (stinging nettle) has become one of the popular alternatives for MSDs as evident from literatures. This systematic review and meta-analysis were conducted to review the stinging nettle’s effectiveness as well as formulations and methods of administration in the MSDs treatment. PubMed, Google Scholar, IIUM Online Library, CINAHL, and OVID were searched for studies from the earliest publication. Mean pain reduction scores included standard mean difference values as a principal outcome measure. The risk of bias and certainty of evidence were assessed based on the Cochrane Handbook Review and GRADEpro tool, respectively. Of seven studies included, the stinging nettle treatment was shown to effectively reduce the musculoskeletal pain with only minor adverse effects were reported (29%). Oral ingestion (57%) and polyherbal formulation (57%) were frequently used in stinging nettle applications. Probable synergistic effect from polyherbal formulation and no definitive effects determined from the single formulations. Hence, there is a need for carefully designed RCTs for stinging nettle preparations in the MSDs treatment to strengthen clinical relevance.